Asas dan Tujuan Perlindungan Anak Dalam Pasal 2 dan 3 Undang-undang No 23 Tahun 2002: Telaah Perspektif Islam - Wahid, Wawan Gunawan Abd. (Sunan Kalijaga State Islamic University & The Asia Foundation, 2006)
People in Indonesia pay more attention to children issues nowadays The Government has made many efforts to anticipate the problems, primarily by issuing the regulations. The newest regulation issued by the Government is regulation number 23 year 2002 on Children Protection. The regulation, which has 14 chapters and 93 articles, includes many important points and one of them is on the principles and goals of children protection, in article 2 and 3. This article shows that within an Islamic perspective the content of those articles is in line with Universal Islamic Norms.